A descriptive study of selected classrooms in the College of Home Economics complex in relation to the students' perception on fire safety in compliance to the educational occupancies required in the fire code of the Philippines - Balankig, Erika Justine W.; Florendo, Raquel B. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
This study provided a descriptive data on the selected classroom within the CHE complex in relation to the students'perception on fire safety in compliance to the Educational Occupancies required in the Fire Code of the Philippines. The investigation was centered on the requirements provided in Section 3. 801 or the General Requirements for Educational Occupancies. Descriptive study was used as the research design, while both quantitative and qualitative methods were used to gather data on the following interior components of the classrooms, such as the exit details, doors, corridors, windows, wall partitions and floors, occupant load, lighting and signs, building service equipment, interior finishes, and fire systems. Purposive sampling was used to determine the three (3) selected classrooms, provided that each one represented a different type - lecture, laboratory, and studio. Fifteen (15) student respondents from each classroom were surveyed on their perception towards the fire safety of the selected classrooms, wherein the students may or may not have issues on the fire safety of the room. Data were gathered through photo documentation, ocular observation, survey questionnaire, and an open-ended interview with the key informant, who provided advises to revisit the concerns related to fire safety. Based from the results of the study, it was perceived that the selected classrooms were identified with both compliant features, e.g. egress accessibility and materiality, and non-compliant features, e.g. fire equipment and component operability. Consequently, this should assist the building management in fortifying the fire safety systems of the interior spaces. The researcher recommends that further studies could be explored on fire safety in interiors and that the building administration could refer to the research on which fire safety details to inspect that may help maximize the fire safety of the interiors as well as the fire resistance of the spaces, readily equipping both the users and the space, itself, during disasters caused by fire.
Thesis (B.S. Interior Design)--University of the Philippines Diliman
Keywords: University of the Philippines. College of Home Economics -- Buildings -- Fires and fire prevention; University of the Philippines. College of Home Economics -- Students -- Attitudes; Fire prevention -- Law and Legislation -- Philippines